2012
DOI: 10.1002/wdev.66
|View full text |Cite
|
Sign up to set email alerts
|

Diseases of the tooth: the genetic and molecular basis of inherited anomalies affecting the dentition

Abstract: In humans, inherited variation in the number, size, and shape of teeth within the dentitions are relatively common, while rarer defects of hard tissue formation, including amelogenesis and dentinogenesis imperfecta, and problems associated with tooth eruption are also seen. In many cases, these anomalies occur in isolation, but they can also present as a feature of numerous well-characterized developmental syndromes. Complex reiterative signaling between the epithelium and mesenchyme is a feature of normal too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 237 publications
(285 reference statements)
0
73
1
4
Order By: Relevance
“…It may occur as part of a recognised genetic syndrome or as a nonsyndromic isolated trait [2]. The condition refers to the developmental failure of six or fewer teeth [3].…”
Section: Definitions and Classificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It may occur as part of a recognised genetic syndrome or as a nonsyndromic isolated trait [2]. The condition refers to the developmental failure of six or fewer teeth [3].…”
Section: Definitions and Classificationsmentioning
confidence: 99%
“…Heterozygous mutations in PAX9, in humans, have been associated with nonsyndromic tooth agenesis [2]. Most recently, a case-control study of 306 unrelated Portuguese individuals found that single nucleotide polymorphisms in the PAX9 gene were associated with a high risk of maxillary lateral incisor agenesis [56].…”
Section: Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Tooth formation is dependent on, and controlled by, the activity of a limited number of conserved secreted signaling proteins (and their downstream pathways), including the TGF-b superfamily, FGFs, Hedgehog, and WNT, 49,3 all of which are commonly exploited in developmental processes during embryogenesis. 50 Certain family members have been shown to mediate reciprocal tissue interactions, and to control the expression of various signals and transcription factors essential for tooth formation.…”
Section: Sema3a As a Link Integrating Organogenesis And Innervationmentioning
confidence: 99%
“…Localised ankylosis between the root and alveolar bone could be one explanation for failure of eruption prior to, during or after complete emergence. 4,5 Estimates of the prevalence of infraocclusion in the primary dentition have ranged between 1.3% and 38.5%. [6][7][8][9] This wide range of variation may be related to differences in study sample sizes, age groups, diagnostic methods and inclusion/exclusion criteria.…”
mentioning
confidence: 99%